Chhattisgarh, India : Performance Rating of Gram Panchayats through Community Score Cards - Murty, J.V.R.; Agarwal, Sanjay; Shah, Parmesh (World Bank, Washington, DC, 2016)
The World Bank-supported Chhattisgarh District Rural Poverty Reduction Project (CGDPRP), also called locally as Nawa Anjor (New Light), aims at improving opportunities for poor and vulnerable communities in Chhattisgarh State. To achieve this goal, the project creates infrastructure and income opportunities for the rural poor, empowers disadvantaged groups, and helps local governments1 become more responsive and effective in assisting the poor. CGDPRP sought to develop a performance monitoring and rating system to build local government capacity, especially the Gram Panchayats (GPs). In this context the project experimented with the use of the Community Score Card (CSC) for identifying crucial issues that affect local service delivery, measure user satisfaction, empower village citizens (especially the poor and women), and rate the performance of GPs. This note summarizes the findings, processes, concerns, and lessons learned from the Chhattisgarh pilot.